The Influence of Professional Competence and Teacher Motivation on Teacher Performance - wijaya, Reni; Yadewani, Dorris (Asean International Journal of Business, 2025)
Purpose – This study aims to determine the professional competence of teachers and teacher motivation towards performance as teachers Methodology/approach – This research method is quantitative descriptive with an ex post facto research approach. The population in this study were PNS/PPPK teachers at elementary schools throughout Lubuk Basung Village, Agam Regency, totaling 104 people. Determination of the number of samples used as objects in this study used the Slovin formula so that a sample of 51 was obtained. The data used were primary data and secondary data. Then the data was processed through computer assistance using the SPSS 26 Program Findings – the results of teacher performance were obtained around 50.1% influenced by professional competence and a Sig value of 0.000 <0.05 so that professional competence has a positive and significant influence on teacher performance. In addition, teacher performance is around 30.6% influenced by teacher motivation and a Sig value of 0.000 <0.05 meaning that teacher motivation has a positive and significant influence on teacher performance. Partially, teacher performance is around 52.5% influenced by the variables of professional competence and teacher motivation with a sig of 0.000 < 0.05 so that Ho is rejected, meaning that there is an influence of professional competence and teacher motivation factors on teacher performance. Novelty/value – Since teacher performance has become an important factor in improving the quality of education, it is important to understand how professional competence and motivation influence teacher performance.